Energy efficient distillation columns sequence for hydrocarbon mixtures fractionation process - Azizan, Mohamad Firdaus (2015)
The objective of this paper is to present the study and analysis of the energy saving improvement for the hydrocarbon mixtures (HM) fractionation process by using driving force method. To perform the study and analysis, the energy efficient HM fractionation plant methodology is developed. Accordingly, the methodology consists of four hierarchical steps; step 1: existing HM sequence energy analysis, step 2: optimal HM sequence determination, step 3: optimal HM sequence energy analysis, and step 4: energy comparison and economic analysis. In the first step, a simple and reliable short-cut method of process simulator (Aspen HYSYS) is used to simulate a base (existing) HM sequence. The energy used to recover individual fractions in the base sequence is analyzed and taken as a reference. In the second stage, an optimal HM sequence is determined by using driving force method. All individual driving force curves for all adjacent components are plotted and the optimal sequence is determined based on the plotted driving force curves. Once the optimal HM sequence has been determined, the new optimal sequence is then simulated in step three using a simple and reliable short-cut method (using Aspen HYSYS), where the energy used in the optimal HM sequence is analyzed. Finally, the energy used in the optimal HMs sequence is compared with the base sequence. The return of investment (ROI) and simple payback period are also calculated. Several case studies have been used to test the performance of the developed methodology. The results show that a maximum energy saving of 40% was achieved when compared the optimal (driving force) sequence with the existing direct sequence. The ROI of 3 was obtained with 4 month of payback period. It can be concluded that, the sequence determined by the driving force method is able to reduce energy used for HM fractionation process. Individual column energy has also been analyzed, and from that several columns that can be improved in terms of energy saving have been identified. All of this findings show that the methodology is able to design minimum energy distillation column sequence for HM fractionation process in an easy, practical and systematic manner.